CRIMINAL CHARACTERISTICS OF COUNTERMEASURES PERFORMED DURING THE INVESTIGATION OF CRIMINAL OFFENSES IN THE SPHERE OF ECONOMIC ACTIVITIES (Bulletin of criminological association of Ukraine, 2024)
Based on the generalization of the conducted scientific searches, it is emphasized that forensic characterization is an information model for the further construction of scientifically based recommendations regarding the investigation of criminal offenses, and its significant theoretical and practical significance is noted. It is proposed to single out such a category as "forensic characteristics of opposition to the investigation." Based on the generalization of theoretical approaches, a basic model of meaningful components of forensic characteristics of criminal offenses in economic activity and characteristics of countermeasures to their investigation is proposed. Mandatory elements of the forensic characteristics of countermeasures to the inquiry include: typed information about the person whocommits the countermeasure and the person about whom it was made, the object that was affected to make it impossible to use it in evidence, and the method of countermeasures, which includes actions against preparation and concealment of the fact of countermeasures. The outlined components are characterized.
Keywords: criminal offense; economic activity; economic crime; resistance to; forensic characteristics